The Rising Tide of Brain Tumours in Nigeria: A Call to Action - Adekunle, Olukorede (Nepal Journal of Neuroscience, 2026)
As a neurosurgeon practicing within the walls of a busy Nigerian tertiary hospital, I am witnessing a quiet but devastating shift in our nation’s epidemiological landscape. Where our wards were once dominated by trauma and infectious pathologies, we are now seeing an unprecedented surge in the incidence of brain tumors. This is no longer a peripheral concern; it is a burgeoning public health crisis that demands immediate attention from the global medical community and national stakeholders.